MUSIC - ITS POSITIVE AND NEGATIVE EFFECTS ON STUDENT HEALTH - Kurbanova Moxigul Shaniyazovna (American Journals, 2025)
Whenever we talk about culture and art, the words of our President, “If we want to know and study real, authentic art, first of all, we must know and study the classical art of maqom. We respectfully commemorate the memory of great poets and thinkers, composers and musicians, and great hafiz who have rendered incomparable service in the formation and development of such a huge spiritual wealth and in the arrival of this eternal art to us,” always ring in my ears. Several decisions of our President in the field of art and culture are an important and bright path for us, the people of art, to be absorbed like a pleasant breeze into our hearts, to serve our field with more joy in our hearts, to approach our field with more love, and to instill the most beautiful qualities in the hearts of future generations through the magic of melody and song.